2020
DOI: 10.4103/jrms.jrms_751_19
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA gene polymorphisms with Type 2 diabetes mellitus: A systematic review and meta-analysis

Abstract: Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder with growing prevalence and increasing economic burden. Based on the role of genetics and epigenetic factors on T2DM, we aimed to carry a systematic review and meta-analysis for all miRNA gene polymorphisms and risk of T2DM. Materials and Methods: A computerized literature search was carried out on PubMed, Web of Science, Scopus, Embase, as well as references of relevant review/meta-analysis. Key search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In our study, a Bonferroni correction was harnessed to confirm our findings. After adjustment, the correlation of rs2910164 with the occurrence of T2DM also existed in overall comparison and in BMI ≥24 kg/m 2 and never drinking subgroups, which was similar to the findings of a more recent meta-analysis [30] . In the future, more well-matched investigations are needed to confirm or refute our observations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, a Bonferroni correction was harnessed to confirm our findings. After adjustment, the correlation of rs2910164 with the occurrence of T2DM also existed in overall comparison and in BMI ≥24 kg/m 2 and never drinking subgroups, which was similar to the findings of a more recent meta-analysis [30] . In the future, more well-matched investigations are needed to confirm or refute our observations.…”
Section: Discussionsupporting
confidence: 87%
“…To determine the potential relationship between miR-SNPs and T2DM, we selected the miR-146a rs2910164 C>G, miR-196a2 rs11614913 T>C and miR-499 rs3746444 A>G loci polymorphism according to the literature, which was significantly associated with cancer ( 20 , 21 , 22 , 23 ), coronary artery disease ( 35 , 36 ) and type 2 diabetes ( 25 , 26 , 27 , 28 , 30 ), in some studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that miR-196a rs11614913 T/C is linked with T2DM [ 29 ]. Downregulation of its mature miRNA may play a pivotal role in T1DM [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that SNP rs11614913 is in MIR196A and is located in chromosome 17 between HOX genes. It also interacts with HOX genes [ 28 , 29 ]. The previous study has shown that HOX genes play a pivotal role in the initiation of fetal organs, including the pancreas.…”
Section: Introductionmentioning
confidence: 99%